2016
DOI: 10.1007/s12325-016-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Use Patterns and Costs of Isolated Limb Perfusion and Infusion in the Treatment of Regional Metastatic Melanoma: A Retrospective Database Analysis

Abstract: IntroductionIsolated limb perfusion and infusion (ILP/ILI) are therapies for regional metastatic melanoma that allow high doses of anticancer drugs to be delivered directly into the circulation of an affected limb, thereby minimizing systemic drug toxicity. This procedure can lead to high response rates and is recommended in patients with Stage III unresectable metastatic melanoma. However, limited information is available on patterns of use and costs. This study examined patterns of ILP/ILI use and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease. [7][8][9][10]12,13,18,37,[39][40][41] The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI. 42,43 The mean LOS for the STS patients who underwent ILP/ILI was slightly longer (7.0 days), and may suggest a higher proportion of patients undergoing ILP, which is typically associated with a longer LOS.…”
Section: Perioperative Outcomessupporting
confidence: 85%
See 1 more Smart Citation
“…However, we defend our approach as necessary in order to minimize surgical procedure variability. Finally, although hypoxic pelvic perfusion is an expensive procedure, costs are similar to those incurred by isolated limb perfusion or infusion procedures for metastatic melanoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data to guide the duration of systemic therapy are lacking [66] and some patients may wish to travel to have a single episode of treatment with ILI or ILP rather than requiring the potentially indefinite administration of systemic therapies, requiring many attendances over a prolonged period. ILP/ILI are relatively expensive, with the mean overall treatment cost calculated at US$36 758 [67]. However, this is very much less than the cost of systemic therapy, which is at least US$100 000 per year [68].…”
Section: Selecting Systemic or Regional Therapymentioning
confidence: 99%